Performance Analysis of Content Based Image Retrivel (International Journal of Engineering and Computer Science, 2017)
This report provides a comprehensive justification on the architectural design of the content based image retrieval system, which adopted the plug-in framework. It presents a thorough explanation of how diverse image feature extraction algorithms were implemented and adopted seamlessly in the system; moreover, it also describes how these algorithms will be dynamically applied in the context of user modifying the query parameters. Furthermore, it illustrates the prominent performance along with accurateness of the system by given that performance metrics and outcome of comparing with other systems. As a final point, it reports the work contribution of team members, and the project management disciplines used to achieve the success of the project.